Pore Pressure Disturbance Induced by Multistage Hydraulic Fracturing in Shale Gas: Modelling and Field Application - Yijin Zeng; Zizhen Wang; Yanbin Zang; Ruihe Wang; Feifei Wang; Xinming Niu; Feng Niu (Geofluids)
Currently, there is no proper method to predict the pore pressure disturbance caused by multistage fracturing in shale gas, which has challenged drilling engineering in practice, especially for the infilling well drilling within/near the fractured zones. A numerical modelling method of pore pressure redistribution around the multistage fractured horizontal wellbore was put forward based on the theory of fluid transportation in porous media. The fracture network of each stage was represented by an elliptical zone with high permeability. Five stages of fracturing were modelled simultaneously to consider the interactions among fractures. The effects of formation permeability, fracturing fluid viscosity, and pressure within the fractures on the pore pressure disturbance were numerically investigated. Modelling results indicated that the pore pressure disturbance zone expands as the permeability and/or the differential pressure increases, while it decreases when the viscosity of the fracturing fluid increases. The pore pressure disturbance level becomes weaker from the fracture tip to the far field along the main-fracture propagation direction. The pore pressure disturbance contours obviously have larger slopes with the variation of permeability than those of the differential pressure. The distances between the pore pressure disturbance contours are smaller at lower permeability and higher viscosity. The modelling results of the updated pore pressure distribution are of great importance for safe drilling. A case study of three wells within one platform showed that the modelling method could provide a reliable estimation of the pore pressure disturbance area caused by multistage fracturing.